Legibility of Safaieh neighborhood in the city of Yazd, Iran - Sadrabadi, Masomeh Roustaei; Ujang, Norsidah; Sadrabadi, Somayeh Roustaei (Faculty of Design & Architecture, Universiti Putra Malaysia, 2017)
Cities are developed to support human activities and well-being. Facilitating human activities depends on the structures and characteristics of the physical elements of cities. In Iranian cities, it is observed that in new urban areas such as Safaieh neighborhood, most residents are facing challenges to find their way around. This is because the physical elements are unable to conjugate the psychological aspects to enhance legibility of the environment. In this respect, scholars and researchers of environmental design and environmental psychology fields argued that there is a strong relationship between arrangement of the physical elements and legibility of the city. To enhance legibility of Safaieh neighborhood, this study aims to identify physical elements and psychological aspects of the urban environment to enrich people’s wayfinding and orientation. The elements can be classified into landmarks, paths, nodes, edges and districts. The study examines the effects of such physical elements on the psychological aspects helps human wayfinding and orientation. The study adopted field observation, questionaire survey and interview to identify physical elements and to examine those effects on people’s wayfinding and orientation in Safaieh neighborhood. The study found that from the perspectives of the respondents, the physical elements are not legible enough to provide clear image for residents to have a good perception of environmental information. The findings assist urban designers to understand the effect of physical elements and to develop strategic plans to enhance the legibility of urban setting. Therefore, the outcome could be used to improve wayfinding and orientation ability of residents in different neighborhoods in Iranian cities.